Analysis of Crystallinity and Physical Properties of the Bio-solar Gemstone - Ismail Ismail; Akmal NIzar; Murzal .; Zulkarnain Jalil (Aceh International Journal of Science and Technology, 2019)
Abstract – Bio-solar is one of the natural gemstones found in the province of Aceh in Indonesia. A recent study suggested that this gemstone could be considered as a vesuvianite type of gemstone. Nevertheless, detail information of this bio-solar gemstone is still unknown. We do not know whether the bio-solar gemstone is crystalline or amorphous. The specific gravity and the hardness of this gemstone are also still unknown. This information is essential to determine the quality of a gem. To answer those questions, we have used x-ray diffraction to study the bio-solar gemstone from the province of Aceh in Indonesia. The physical properties (specific gravity and hardness) of this gemstone have also been measured. We found that the bio-solar gemstone is composed by CaO, SiO2, MgO, Al2O3, Fe2O3, and TiO2 phases. Our results revealed that the bio-solar gem is a crystalline material, not amorphous. The average crystallite size of this gemstone is found to be 353 Å (35 nm). Moreover, the specific gravity of bio-solar gemstone is found to be 3.09 – 3.34. Its hardness is 3 to 4 mohs. Thus, the bio-solar is a good quality gemstone. Our finding confirmed that the bio-solar could be classified as a vesuvianite gemstone.